2004
DOI: 10.1016/j.bmcl.2003.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of thiophene-2-carboxylic acids as potent inhibitors of HCV NS5B polymerase and HCV subgenomic RNA replication. Part 1: Sulfonamides

Abstract: The discovery of a novel class of HCV NS5B polymerase inhibitors, 3-arylsulfonylamino-5-phenyl-thiophene-2-carboxylic acids is described. SAR studies have yielded several potent inhibitors of HCV polymerase as well as of HCV subgenomic RNA replication in Huh-7 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 20 publications
(4 reference statements)
2
21
0
Order By: Relevance
“…As controls (Fig. 1D), compounds with known activities against HCV RdRp (LCY967) (8), polymerases ␣ (aphidicolin) (17), and polymerases ␤ (lithocholic) (31) showed expected anti-polymerase results, with IC 50 s of 50 nM, 40 M, and 40 M, respectively. These results indicate that NITD-2 selectively inhibits DENV-2 polymerase.…”
Section: Resultsmentioning
confidence: 96%
“…As controls (Fig. 1D), compounds with known activities against HCV RdRp (LCY967) (8), polymerases ␣ (aphidicolin) (17), and polymerases ␤ (lithocholic) (31) showed expected anti-polymerase results, with IC 50 s of 50 nM, 40 M, and 40 M, respectively. These results indicate that NITD-2 selectively inhibits DENV-2 polymerase.…”
Section: Resultsmentioning
confidence: 96%
“…[11][12][13][14][15][16][17] Recently, many non-nucleoside inhibitors (NNIs) of HCV NS5B RNA polymerase have been discovered. [18][19][20][21][22][23][24][25][26][27][28][29] Structural studies of HCV NS5B polymerase genotypes 1b and 2a in complex with phenylalanine, dihydropyranone, thiophene, and indole-based non-nucleoside analogue inhibitors bound non-covalently have also been carried out. [30][31][32][33][34] These studies revealed that phenylalanine, dihydropyranone and thiophene-based non-nucleoside inhibitors bind to a common predominantly hydrophobic depression in the thumb domain, that is located approximately 35 Å from the polymerase active site.…”
Section: Introductionmentioning
confidence: 99%
“…1). These inhibitors were synthesized as part of ongoing structure-activity relationship optimization efforts that have been described elsewhere (21)(22)(23). The details of the inhibitor binding site, protein-inhibitor interactions, and plausible mechanisms of inhibition will be discussed in the second part of the paper.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%